Temporal patterns of loneliness and their associations with mental health outcomes: Observations from a longitudinal study - Błażej Misiak; Paweł Liśkiewicz; Jerzy Samochowiec (European Psychiatry)
Abstract Background Loneliness is a global public health concern. Investigating loneliness in the general population offers a greater generalizability across various levels of health-related impairments, the identification of at-risk individuals, the detection of different loneliness severity levels, and broader insights into social determinants. Previous studies have shown that loneliness might be a transient or chronic experience, depending on how consistently it is reported across at least two timepoints. This study aimed to assess differential associations of chronic and transient with various domains of psychopathology.